Investigation of the susceptibility rates to ceftazidime-avibactam and colistin, clonal relationships, and clinical data of patients with carbapenem-resistant Klebsiella pneumoniae isolates detected in the ICUs of a hospital in İstanbul - Akkaya, Yuksel; Aydin, Irfan; Harmankaya, Sebile; Karakul, Mehmet; Aydin, Mehtap; Erdin, Begum Nalca; Kilic, Ibrahim Halil (K Faisal Spec Hosp Res Centre, 2026)
BACKGROUND: The increase in carbapenem-resistant K. pneumoniae (CR-Kp) in intensive care units (ICUs) causes treatment difficulties and increases risk in mortality. OBJECTIVES: The aim of this study was to investigate the susceptibility rates of CR-Kp isolates obtained from ICUs to ceftazidime-avibactam (CAZ-AVI) and colistin, carbapenem resistance genes, clonal relationships and clinical characteristics of the patients. DESIGN: Retrospective cohort SETTING: Single-center, University of Health Sciences, & Uuml;mraniye Training and Research Hospital MATERIALS AND METHODS: This study was conducted between June 2023 and December 2024. Isolates were identified using VITEK MS v.3.2, and antibiotic susceptibility testing was performed using the VITEK 2 Compact system. CAZ-AVI susceptibility was determined using disk diffusion, and colistin susceptibility was determined using broth microdilution to determine minimum inhibitory concentration (MIC) values. Carbapenem resistance genes were determined using multiplex real-time polymerase chain reaction (RT-PCR) and clonal relationship arbitrarily primed-polymerase chain reaction (AP-PCR). MAIN OUTCOME MEASURES: Resistance genes of CR-Kp isolates, clonal relationships, CAZ-AVI and colistin resistance, and clinical characteristics of patients SAMPLE SIZE: Ninety-seven isolates from 76 patients RESULTS: Among patients with CR-Kp isolates, central venous catheter use was detected in 59 cases (78%), ventilator-associated pneumonia in 44 cases (58%), and bacteremia in 39 cases (51%), respectively. It was determined that 53 of the patients (70%) died. Using the AP-PCR method, 60 different genotypes were identified among 97 isolates, and clustering was determined in 42 of the isolates (46%). It was determined that 36 (37%) of the isolates were resistant to colistin and 42 (45%) were resistant to CAZ-AVI. NDM+OXA-48, OXA-48, KPC, KPC+NDM, and NDM genes were detected in 40 (43%), 32 (35%), 10 (11%), 2 (2%), and 3 (3%) isolates, respectively. It was determined that 30 (75%) of the isolates with NDM+OXA-48 and only 4 (12%) of the isolates with OXA-48 were resistant to CAZ-AVI. CONCLUSION: In addition to OXA-48, an increase in the frequency of CR-Kp isolates containing the NDM, NDM+OXA-48, KPC+NDM, and OXA-48+KPC genes were also detected. It was also determined that resistance to colistin and CAZ-AVI is increasing. The AP-PCR method can also be used to investigate infections. LIMITATIONS: Single center,Pulsed Field Gel Electrophoresis (PFGE) could not be performed together with AP-PCR
Keywords: CR-Kp; CAZ-AVI; carbapenemase genes; clonal relationship; colistin